KOMUNIKASI INTRAPERSONAL MELALUI MEDITASI: STUDI FENOMENOLOGI DI INSTAGRAM @PISHIYOGA - Hape, Virnica Amanda; Nurfalah, Farida; Lestari, Aghnia Dian (Universitas Swadaya Gunung Jati, 2023)
Humans as individual beings must have awareness of their thoughts and behaviour so that they can find balance and self-concept, therefore humans need to carry out intrapersonal communication optimally and one form of embodiment of intrapersonal communication is through meditation. Researchers use Instagram @pishiyoga as a media for meditation because it has a level of flexibility. The purpose of this study was to find out the process of intrapersonal communication through meditation on Instagram @pishiyoga. The data sources used in this paper are primary and secondary data. The research method used is a phenomenologic qualitative approach which aims to reduce individual experience to get the essentials. Primary data in the study were obtained from full participation observations involving researchers as research subjects and interviews, while secondary data were obtained from literature and documentation to support the data that had been obtained. Data collection methods used are observation, in-depth interviews and documentation. Data analysis was carried out through data reduction, data presentation, data verification and conclusion. The results of the study show that the process of intrapersonal communication through meditation is interpreted as a process of finding identity, a process of gaining awareness, and as a necessity in the process of self-healing which is intended to obtain the formation of a personality. positive self-concept. Keywords: Intrapersonal Communication, Meditation, Self Awareness